WATER-SAVING AMONG SCHOOL STUDENTS IN MALAYSIA - Mohmadisa Hashim; Mohamad Danial Mohd Shariff; Hanifah Mahat; Saiyidatina Balkhis Norkhaidi; Nasir Nayan; Yazid Saleh (Jurnal Cakrawala Pendidikan, 2021)
A study was conducted among school students in Baling district, Kedah to study their level of knowledge, attitude, and practice regarding water-saving. A quantitative approach was adopted by survey instrument. The study sample consisted of 144 students, selected based using simple random sampling technique while stratified random technique was used to select school. Pearson’s correlation and t-test were used used to analyse the data. Based on the findings, it was found that the level of knowledge and the level of attitude were high in water-saving, while the water-saving practice was at a moderate level. The t-test results showed that knowledge, attitude, and practice did not have a significant difference in water-saving. The results of the Pearson’s correlation showed a moderately positive relationship between the water-saving knowledge and water-saving practice and a moderately positive relationship between water-saving attitude and practice. Overall, it can be concluded that the students had a high level of knowledge and attitude in water-saving. However, water-saving practice was still at a moderate level, and students need to improve their water-saving practice from time to time.